STRATEGI MARKETING PUBLIC RELATIONS MELALUI MEDIA SOSIAL DALAM MEMBANGUN BRAND AWARENESS - Eva Nuraeni; Ari Pandu Witantra; Andin Nesia (Jurnal Riset Komunikasi Terapan, 2024)
This research is motivated by the increasing development of technology which can now make the work of a Public Relations person easier, by utilizing social media. To build Brand Awareness, the right strategy is needed. This research aims to find out how Marketing Public Relations Strategy through social media builds Brand Awareness (Study on the official Instagram account@nasikulitmalamminggu) This research uses Marketing Public Relations and is supported by the Three ways Strategy concept from Thomas L. Harris (1991). This research is descriptive qualitative in nature, using a case study method, data collection techniques through in-depth interviews, observation and documentation. The results of this research show that the marketing public relations strategy carried out by Nasi kulit Malam Minggu is: Pull strategy, actively publish via social media Instagram regarding activities that are being carried out, provide several promotions  and  actively  collaborate  with  various  well-known  brands.  Special  event  Push Strategy  participated  in  the  IFRA  2023  exhibition,  providing  endorsements  to  several influencers.  Pass  strategies  through  Corporate  Social  Responsibility  (CSR)  activities  in collaboration with the community.Keywords: Brand awareness, Marketing Public Relations, Nasi Kulit Malam Minggu